“Revocatoria del Mandato de dignatarios electos mediante votación popular en los Gobiernos Autónomos Descentralizados y su impacto jurídico, social y económico”. - Ortega Samaniego, Alvaro Josué (2024)
This paper, titled "Recall of Elected Officials through Popular Vote in Decentralized Autonomous Governments and Its Legal, Social, and Economic Impact," aims to study the legal institution of mandate recall. It traces its origins in our country and analyzes how it functions in other nations around the world. The goal is to determine the reasons why, in various countries—particularly in Ecuador—such processes have lost relevance, largely due to distrust in electoral bodies and political systems. Additionally, the economic burden of such large-scale processes and the difficulty in meeting the established requirements have resulted in many recall efforts being reduced to mere formalities. In the specific case of Ecuador, this study examines doctrine, legislation, and real-life cases. Through various research methods, it concludes that true citizen participation must be grounded in solid political education. Moreover, it emphasizes the need for citizens to exercise their power in holding electoral institutions accountable, ensuring that participation rights are properly respected. Finally, this paper proposes that any proper execution of a mandate recall should include reforms preventing those who have been removed from office from running for re-election through popular vote.